Morphotype-Dependent Flow Characteristics in Bicuspid Aortic Valve Ascending Aortas: A Benchtop Particle Image Velocimetry Study - McNally, Andrew; Madan, Ashish; Sucosky, Philippe (Frontiers in Physiology, 2017)
The bicuspid aortic valve (BAV) is a major risk factor for secondary aortopathy such as aortic dilation. The heterogeneous BAV morphotypes (left-right-coronary cusp fusion (LR), right-non-coronary cusp fusion (RN), and left-non-coronary cusp fusion (LN)) are associated with different dilation patterns, suggesting a role for hemodynamics in BAV aortopathogenesis. However, assessment of this theory is still hampered by the limited knowledge of the hemodynamic abnormalities generated by the distinct BAV morphotypes. The objective of this study was to compare experimentally the hemodynamics of a normal (i.e., non-dilated) ascending aorta (AA) subjected to tricuspid aortic valve (TAV), LR-BAV, RN-BAV, and NL-BAV flow. Tissue BAVs reconstructed from porcine TAVs were subjected to physiologic pulsatile flow conditions in a left-heart simulator featuring a realistic aortic root and compliant aorta. Phase-locked particle image velocimetry experiments were carried out to characterize the flow in the aortic root and in the tubular AA in terms of jet skewness and displacement, as well as mean velocity, viscous shear stress and Reynolds shear stress fields. While all three BAVs generated skewed and asymmetrical orifice jets (up to 1.7- and 4.0-fold increase in flow angle and displacement, respectively, relative to the TAV at the sinotubular junction), the RN-BAV jet was out of the plane of observation. The LR- and NL-BAV exhibited a 71% increase in peak-systolic orifice jet velocity relative to the TAV, suggesting an inherent degree of stenosis in BAVs. While these two BAV morphotypes subjected the convexity of the aortic wall to viscous shear stress overloads (1.7-fold increase in maximum peak-systolic viscous shear stress relative to the TAV-AA), the affected sites were morphotype-dependent (LR-BAV: proximal AA, NL-BAV: distal AA). Lastly, the LR- and NL-BAV generated high degrees of turbulence in the AA (up to 2.3-fold increase in peak-systolic Reynolds shear stress relative to the TAV) that were sustained from peak systole throughout the deceleration phase. This in vitro study reveals substantial flow abnormalities (increased jet skewness, asymmetry, jet velocity, turbulence and shear stress overloads) in non-dilated BAV aortas, which differ from those observed in dilated aortas but still coincide with aortic wall regions prone to dilation.